DIGITAL LITERACY MODEL TO IMPROVE THE MARKETING SKILLS OF MSME WOMEN WITH A COMMUNITY-BASED EDUCATIONAL APPROACH - Helmi, Sulaiman; Setyadi, Bakti; Wedadjati, Ratna S.; AM, Muh. Asriadi; Yahya, Nurhidayah (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This study uses a community-based approach to develop an educational model for digital literacy among MSME women. Employing a qualitative case study method with 15 informants from the Indonesian Muslim Entrepreneurs Association Palembang MSME Community, data was obtained through interviews and analyzed thematically. The findings, indicating that most female members have at least a high school education and less than five years of business experience, highlight challenges in digital literacy and marketing skills. These challenges, including difficulties in technology adoption and security concerns, underscore the necessity for initiatives to enhance digital literacy and marketing skills. A community-centric model is proposed, encompassing Digital Literacy Workshops, Mentor-Mentee Programs, Sharing Sessions, Best Practices, and Specific Skills Training, with interview conclusions serving as a basis for model design to elevate Marketing Skills effectively